Subsidies and agricultural productivity: CAP payments and labour productivity (convergence) in EU agriculture - Maria Garrone; Dorien Emmers; Alessandro Olper; Johan F. M. Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2018)
This paper investigates the relationship between EU agricultural subsidies and agricultural labour productivity by estimating a conditional growth equation. We use more representative subsidy indicators and a wider coverage (panel data from 213 EU regions over the period 2004-2014) than have been used before. We find that, on average, CAP subsidies increase agricultural labour productivity, and the effect is almost entirely due to decoupled Pillar I payments. Coupled Pillar I payments have no impact. The impact of Pillar II is mixed.
Keywords: 330